Brain potentials associated with conscious aftereffects induced by unseen stimuli in a blindsight subject. - Weiskrantz, L; Rao, A; Hodinott-Hill, I; Nobre, A; Cowey, A (2003)
The study is of brain activity in a blindsight subject (D.B.), who reports conscious visual afterimages of stimuli of which he is unaware when they are presented. This contrast offered a unique opportunity to study event-related potential recordings of conscious versus unconscious visual phenomena generated by the very same stimulus in the identical locus of the visual field. The behavioral results confirmed the reliability of the difference in the subject's report for inducing stimuli versus their aftereffects. The rationale of the event-related potential analysis was to subtract "on" signals from "off" signals, the latter associated with the onset of conscious events and the former for events that remained unconscious. Because there are inherent differences in on and off potentials, the subtractive resultants for the blind hemifield were compared with the same subtractions for the good hemifield when the subject was aware both of the stimuli and their afterimages. A differential pattern in subtractive resultants emerged with a strong anterior left frontal focus for the blind field and a posterior focus for the intact field. The results are compared with other studies suggesting an anterior focus for conscious visual events.